Clinicopathological significance of heterogeneic ezrin expression in poorly differentiated clusters of colorectal cancers. Issue 8 (22nd June 2019) - Aikawa, Akane; Fujita, Hideto; Kosaka, Takeo; Minato, Hiroshi; Kiyokawa, Etsuko
Abstract: Multicellular structures, such as tumor buddings and poorly differentiated clusters (PDC), exist at the invasive front of colorectal cancers (CRC). Although it has been reported that CRC with PDC showed frequent lymph node metastases with a worse prognosis, the molecular markers of PDC that are responsible for prognosis have not been identified. We here noticed for the first time that Ezrin, a regulator of the actin cytoskeleton, is expressed in the corner cells of PDC. We then aimed to verify whether heterogeneous Ezrin expression in PDC predicts the prognosis of CRC patients. We immunohistochemically analyzed Ezrin expression in PDC of 184 patients with completely resected stages I‐III CRC. We established the Ezrin corner score (ECS), which quantifies the tendency of Ezrin‐positive cells to accumulate at the corners of PDC. On the basis of ECS values, 2 indices, the mean ECS and the number of PDC with high ECS, were obtained. Both indices were significantly higher in CRC with lymphatic invasion, higher PDC grade, and presence of micropapillary (MP) PDC. The mean ECS‐high group showed shorter recurrence‐free survival than the mean ECS‐low group but without significance. The other index, the number of ECS‐high PDC, was significantly associated with recurrence‐free survival. These results suggest that Ezrin is involved in PDC progression and lymphatic invasion, and that ECS may be a marker for aggressive PDC. Abstract : The Ezrin corner score was calculated for heterogeneous Ezrin expression in PDC. The number of ECS‐high PDC was significantly associated with recurrence‐free survival.